О методах получения прозрачных проводящих алмазоподобных углеродных пленок и о механизмах формирования в них проводимости - Ж. Р. Паносян; А. Т. Дарбасян; С. С. Восканян; Е. В. Енгибарян (ՀՀ ԳԱԱ հրատ.)
Разработана технология получения прозрачных проводящих алмазоподобных углеродных пленок. Проводимость в пленках получена при легировании азотом в процессе роста или предварительным нанесением на подложку катализаторов роста наноструктур. Technology for obtaining transparent conductive diamond-like carbon films has been developed. Conductivity of the films is ensured by doping with nitrogen during the growth process or by preliminary application of a metal catalyst on the substrate for further growth of nanostructures.
Keywords: Physics; Science; Radiophysics